Terlantarnya Rel Kereta Api Di Batipuh Dalam Seni Grafis - Athallah Naufal; Ariusmedi Ariusmedi (Pendekar : Jurnal Pendidikan Berkarakter, 2024)
The purpose of creating this work is as a social criticism and conveying a message regarding the abandonment of the railroad tracks in Batipuh. It is feared that the abandonment of the railway tracks will have a negative impact on the assets of the railways, the people who live on the edge of the railway tracks which will change the use of the station buildings and railway tracks. In order to prevent this from happening, the author was inspired to visualize the negative impact of abandoned railway tracks which were converted into use by the community which was outlined in graphic art works. The creation of the work used the art consortium method with five stages, namely, the preparation stage (observing and exploring), the elaboration stage ( searching for and collecting references), the synthesis stage (application of the idea/main idea), concept realization (creating the work), and the completion stage (in the form of a report and exhibition of the final work). So that the author created ten works with the theme of the impact of abandoned railroad tracks. The resulting works were 10 works with a size of 60 x 40 cm with titles including: Food, Garage, Landfill, Steel Park, Short Road, Buried Asphalt, Distribution, Cloud Top Grass, Toothed Rail, Kadai Katupek.